Stimulation of dendritic cells with vaccine and vaccineantibody complex and effect on immune response - (:unkn) unknown (My University, 2013)
0

Dendritic cell (DC) vaccines are a promising and potent therapeutic tool for chronic diseases, autoimmune diseases, and cancer because of the unique ability of DCs to stimulate T cells. The challenge of DC vaccines is to find an effective form for antigen presentation. Although pure antigens, antigen complexes, plasmids, and mRNA have been used in different studies, no proper application to overcome this problem has been found yet. In this study, we investigated the eligibility of a commercial hepatitis B virus (HBV) vaccine or a vaccine monoclonal antibody complex for antigen loading of DCs for a therapeutic purpose. DCs were derived from the bone marrow of transgenic hepatitis B (HBV-tg) mice using a granulocyte macrophage-colony stimulating factor and interleukin-4, and then loaded with a commercial HBV vaccine (containing hepatitis B virus surface antigens and aluminum hydroxide adjuvant) or a vaccine antibody complex. HBV-tg mice were immunized with the vaccine and vaccine antibody loaded DCs. Optimum HBV vaccine concentration and loading time were determined by 2-(4-iodophenyl)-3-(4-nitrophenyl)-5-(2,4-disulfophenyl)-2H-tetrazolium (WST- 1) methods. Therapeutic effects of vaccine antibody loaded DCs were determined by the evaluation of antibody response and hepatitis B surface expression levels in HBV-tg mice. Our results showed that commercial HBV vaccine loaded DCs induced humoral response in HBV-tg mice but had no effect on cellular immunity.
Keywords: Biyoloji